THE RELATIONSHIP OF LEADERSHIP AND MOTIVATION TO THE PERFORMANCE OF BAH KAPUL PUSKESMAS EMPLOYEES IN THE WORKING AREA OF SIANTAR SITALASARI SUB-DISTRICT PEMATANGSIANTAR CITY - Riada Mareny (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
An organization must have a leader who is able to influence, direct and guide employees in the organization. The relationship between motivation and employee performance is that the higher the motivation of employees in work, the resulting performance is also more effective and competent in their field. The performance value of Puskesmas employees in North Siantar Sub-District is low, namely the coverage of health service outcomes with an achievement level of ≤80%. This study aims to determine the relationship between leadership and motivation with the performance of employees of the Bah Kapul Health Center in Siantar Sitalasari District, Pematangsiantar City in 2017. The design of this study was cross-sectional analytic with a sample size of 4 1 person. Samples were taken using the Total Population Sampling technique. The data collection tool was a questionnaire and data analysis was carried out using univariate and bivariate (chi-sguare) methods. The results showed that there was a significant relationship between leadership and the performance of Bah Kapul Health Center employees in Siantar Sitalasari District, Pematangsiantar City in 2017, the P Value was 0.029 < α (0.05) and there was a significant relationship between motivation and the performance of Bah Kapul Health Center employees in Siantar District Sitalasari City of Pematangsiantar In 2017, the P Value was 0.002<α (0.05). It is hoped that consistent and continuous training will improve the management capabilities of the head of the puskesmas and motivate employees so that they are able to improve performance. The results showed that there was a significant relationship between leadership and the performance of Bah Kapul Health Center employees in Siantar Sitalasari District, Pematangsiantar City in 2017, the P Value was 0.029 < α (0.05) and there was a significant relationship between motivation and the performance of Bah Kapul Health Center employees in Siantar District Sitalasari City of Pematangsiantar In 2017, the P Value was 0.002<α (0.05). It is hoped that consistent and continuous training will improve the management capabilities of the head of the puskesmas and motivate employees so that they are able to improve performance. The results showed that there was a significant relationship between leadership and the performance of Bah Kapul Health Center employees in Siantar Sitalasari District, Pematangsiantar City in 2017, the P Value was 0.029 < α (0.05) and there was a significant relationship between motivation and the performance of Bah Kapul Health Center employees in Siantar District Sitalasari City of Pematangsiantar In 2017, the P Value was 0.002<α (0.05). It is hoped that consistent and continuous training will improve the management capabilities of the head of the puskesmas and motivate employees so that they are able to improve performance. 05) and there is a significant relationship between motivation and performance of Bah Kapul Community Health Center staff in Siantar Sitalasari District, Pematangsiantar City in 2017, the P Value is 0.002 <α (0.05). It is hoped that consistent and continuous training will improve the management capabilities of the head of the puskesmas and motivate employees so that they are able to improve performance. 05) and there is a significant relationship between motivation and performance of Bah Kapul Community Health Center staff in Siantar Sitalasari District, Pematangsiantar City in 2017, the P Value is 0.002 <α (0.05). It is hoped that consistent and continuous training will improve the management capabilities of the head of the puskesmas and motivate employees so that they are able to improve performance.